GluN2D NMDA Receptors Gate Fear Extinction Learning and Interneuron Plasticity - Dubois, Christophe J.; Liu, Siqiong June (Frontiers in Synaptic Neuroscience, 2021)
The cerebellum is critically involved in the formation of associative fear memory and in subsequent extinction learning. Fear conditioning is associated with a long-term potentiation at both excitatory and inhibitory synapses onto Purkinje cells. We therefore tested whether fear conditioning unmasks novel forms of synaptic plasticity, which enable subsequent extinction learning to reset cerebellar circuitry. We found that fear learning enhanced GABA release from molecular layer interneurons and this was reversed after fear extinction learning. Importantly an extinction-like stimulation of parallel fibers after fear learning is sufficient to induce a lasting decrease in inhibitory transmission (I-LTDstim) in the cerebellar cortex, a form of plasticity that is absent in naïve animals. While NMDA receptors are required for the formation and extinction of associative memory, the role of GluN2D, one of the four major NMDA receptor subunits, in learning and memory has not been determined. We found that fear conditioning elevates spontaneous GABA release in GluN2D KO as shown in WT mice. Deletion of GluN2D, however, abolished the I-LTDstim induced by parallel fiber stimulation after learning. At the behavioral level, genetic deletion of GluN2D subunits did not affect associative learning and memory retention, but impaired subsequent fear extinction learning. D-cycloserine, a partial NMDA receptor agonist, failed to rescue extinction learning in mutant mice. Our results identify GluN2D as a critical NMDAR subunit for extinction learning and reveal a form of GluN2D-dependent metaplasticity that is associated with extinction in the cerebellum.